Strengthening China's and India's trade and investment ties to the Middle East and North Africa. (Orientations in development., 2009)
China and India's spectacular economic rise over the last two decades has accelerated their trade and investment flows with the Middle East and North Africa (MENA), particularly with the oil-producing countries. And while these flows are still small, China and India's presence in the region is on the rise. This report focuses on the following questions: what have been evolution and the impact of MENA's trade and investment relations with China and India? what actions can be taken to maximize the benefits from these relations and to enhance MENA's international integration? The main findings indicate that the region as a whole has benefited from the rise of China and India in terms of better terms of trade, significant increases in oil and gas exports, and cheaper imports. However, producers of industrial goods have been negatively--and in a few cases severely--affected by competition with the two Asian countries in both third and domestic markets. While China and India are investing more in MENA, they are contributing very little to job creation or to the transfer and diffusion of technology. Faster growth in the two Asian countries--and the associated higher demand for energy--will increase revenues from oil and the difficult choices associated with their management. For the labor-abundant, non oil-producing countries, competition with China and India will increase. But the lack of competitive manufacturing industries and services, the insufficient attention given in the past to building technological capabilities and promoting openness and entrepreneurship are constraining their ability to respond to competition. They need to accelerate productivity to tackle unemployment, especially among youth. This may require the broader institutional changes seen in China and India--suggesting the importance of a pragmatic reform agenda that can accelerate productivity, trade, and investment in the region.--Publisher description.